Inclusion of Melatonin in Semen Extender Modulates Post Thaw Motility and Velocity Pa-rameters of Mithun Sperm - Perumal, P. (International Journal of Bio-resource and Stress Management, 2019)
Melatonin (MT) has significant function on seasonal reproduction and circadian clock regulation in the mammals. It also a powerful antioxidant and anti-apoptotic compound in semen cryopreservation. Environmental parameters like day-length, temperature and relative humidity are important factors to determine the variation in semen production, its quality profiles and fertilizing ability of the sperm. Therefore, a study was designed to assess MT effect on mobility and velocity parameters by computer assisted sperm analyser (CASA) at different seasons in mithun. Total of 80 ejaculates (20 ejaculates per season) were collected from mithun twice per week by transrectal massage method and ejaculates were grouped into six equal, processed and diluted with standard Tris-egg yolk-citrate-glycerol-extender (TEYCGE). Gr1: extender without additives (control), Gr 2 to 6: extender extended with MT 1, 2, 3, 4 and 5 mM, respectively. CASA profiles were measured in frozen thawed semen. Addition of MT in the extender has significantly (p<0.05) minimized the static velocity or dead spermatozoa, simultaneously significant improvement was in sperm total motility (TM), forward progressive motility (FPM), average path velocity (VAP), curvilinear velocity (VCL), straight line velocity (VSL), amplitude of lateral head displacement (ALH), beat cross frequency (BCF), straightness (STR), linearity (LIN) and rapid velocity in treatment as compared to control group at different seasons of the year. The present study result clearly indicated that melatonin protected the post thaw CASA parameters in different seasons and also semen quality varied from different seasons and was significantly higher in spring and lowest was in summer season.